Analysis of Transferred MoS2 Layers Grown by MOCVD: Evidence of Mo Vacancy Related Defect Formation. (7th April 2020) - Schoenaers, B.; Leonhardt, A.; Mehta, A. N.; Stesmans, A.; Chiappe, D.; Asselberghs, I.; Radu, I.; Huyghebaert, C.; De Gendt, S.; Houssa, M.; Afanas'ev, V. V.
Abstract : A low-temperature multi-frequency electron spin resonance (ESR) study has been carried out on 1, 3.5, and 6 layer thick MoS2 films, grown by metal organic vapor deposition (MOCVD) and subsequently transferred on SiO2 /Si. This reveals the observation of a previously unreported, nearly isotropic signal at g ≈ 1.9998 with corresponding spin center (spin S = ½) densities ranging from ∼6 × 10 8 cm −2 to ∼5 × 10 11 cm −2 . The ESR investigation is closely combined with an in-depth analysis by an assortment of other experimental techniques, including atomic force microscopy (AFM), Rutherford backscattering spectrometry (RBS), X-ray photoelectron spectroscopy (XPS), and transmission electron microscopy (TEM), to ultimately result in the assignment of the ESR signal to a defect of intrinsic nature, most likely a Mo vacancy (VMo ) related defect located at MoS2 grain edges or boundaries. The oxidation of the 2D material at grain edges and boundaries combined with the applied water-based transfer procedure is demonstrated to play a crucial role in the generation of the newly observed defect, thus advising caution with the currently applied process method. The presented analysis, which combines a variety of experimental techniques, contributes to the fine-tuning of the CVD growth and transfer process of high-quality few-layer MoS2 intended for next-generation nanoelectronic devices.